Ligand exchange processes on solvated beryllium cations, VI. Hydrogen chalcogenide exchange on [Be(Chelate)Sol2]2+ (Chelate: CH3-O-C2H4-O-CH3, CH 3-S-C2H4-S-CH3, CH 3-Se-C2H4-Se-CH3; Sol: H 2O, H2S, H2Se) - Walther, Markus; Dücker-Benfer, Carlos; Puchta, Ralph (Zeitschrift für Anorganische und Allgemeine Chemie, 2011)
Following work from Dehnicke et al. on the binding of Be2+ to crown ethers, solvent addition, and solvent exchange energies were calculated (B3LYP/6-311+G**) for solvated beryllium complexes with bidentate ligands CH3-O-C2H4-O-CH3 [1,2-bis(methoxy)ethane], CH3-S-C2H4-S-CH 3 [1,2-bis(methio)ethane], and CH3-Se-C2H 4-Se-CH3 [1,2-bis(methylselanyl)ethane], and H 2O, H2S, and H2Se as solvents. All water exchange reactions for the different bidentate ligands show no variation, with energies of addition to the second coordination sphere of around -25 kcal·mol-1 and exchange activation energies of around 19 kcal·mol-1. Substituting water by H2S and H 2Se in [(CH3-O-C2H4-O-CH 3)Be(Solvent)2]2+ lowered the energy for addition of a solvent molecule in the second coordination sphere to -12 kcal·mol-1 and the exchange activation energy to 12 kcal·mol-1. All reaction mechanisms were found to be of the associative interchange (Ia) type. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Beryllium; Density functional calculations; Ether; Quantum-chemical calculations; Solvent exchange